Auteurs antiques et Antiquité dans les bibliothèques bretonnes à la fin du Moyen Âge et au début de la Renaissance - Lémeillat, Marjolaine (Pecia, 2018)
Abstract Thirty-nine manuscripts containing works by ancient authors and another eight about Antiquity are documented in libraries in Brittany at the end of the Middle Ages. They were owned by eighteen different individuals (fifteen from the nobility, of which eleven were already known as bibliophiles). These books are mostly about Roman Antiquity, consisting of titles from Cicero, Livy and Valerius Maximus. Some are translations from Latin into French. In addition, a few titles about a same subject may have been bound into the same volume. These books have many origins: acquisitions, gifts and confiscations from religious orders. However, their owners, although born into important families of Brittany, lived mostly in France or were in the king of France’s service. Interest in the Antiquity does not seem to have been a Breton peculiarity.